Parental knowledge and awareness and towards allergy prevalence in Selangor - Tengku Azhar, Tengku Norbaya; Che Hassan, Muhamad Rahimi; Mohd Zazi, Norhafizah; Abd Wahab, Noor Akmal; Idris, Saiyidatul Nadiah; Ishak, Nur Syakireen; Abdul Ghani, Radiah (Science & Engineering Research Support Society (SERSC), 2020)
The allergy epidemiology is another worldwide problem as its prevalence trigger troublesome amongst society. Malaysia as a developing country has no exception towards it. Family as a fundamental institution as well as the simplest unit of the society have significant roles to put a bridle on the issues. Allergies are known to cause social and economic burden of the sufferer and to the close family member. Parental knowledge, attitude and practice plays a crucial role in allergy prevalence, prevention and treatment strategy. In Malaysia, the misconception of certain allergy symptom and prevention becomes another real challenge. Poorly self-perceives as the early diagnosis approach could lead to improper clinical diagnosis thus affects the treatment accuracy. It then brings about the delay of appropriate treatment and upturn the treatment cost. In certain urgent allergy conditions, such as anaphylaxis, a delay is lethal to the sufferer. This paper highlights the paternal and maternal knowledge, awareness and practice towards allergy disease. This study also presents the important of having adequate knowledge to self-perceive of allergy disease. As this approach is useful to give surface overview on allergy prevalence, adequate knowledge compromises of precise manifestation. This cross-sectional study involves 117 pair of parents in Selangor with the age ranged from 28-61 years old. A self-administered questionnaire has been used to indicate respondent’s allergy status, their knowledge, awareness and practice towards allergy disease. As overall, the common symptom of allergy among parents were allergy rhinitis, eczema and dry and itchy rashes at skin with the percentage of prevalence ranged between 6.8% to 28.4%. The data also indicated the effect on insufficient of knowledge and awareness among parents towards their decision on treatment and prevention plan. Most parents do not have adequate understanding on the relatedness of immune system abnormality reaction of allergy as well as the roles of immune system component such as Immunoglobulin E (IgE) in allergy reaction. They also have insufficient knowledge about the crucial allergy mechanism such as the cross-reaction activity and the difference between food allergy and food intolerances. Pearson correlation between knowledge of allergy term, cause and symptom with allergy prevention and treatment shows positive significant correlation with (r = 0.244, P=0.008) for maternal and (r = 0.262, P=0.004) for paternal respectively. Parents with inadequate knowledge about allergies symptom have limited ability to choose the treatment and prevention for allergy disease. As the shortcoming, they tend to do unnecessary dietary elimination and extreme food avoidance as well as disregards the important to consult with the healthcare professional regarding their allergy symptom. Overall, parental knowledge in society represent their involvement in prevention and treatment strategy for allergy sufferer especially their children. Adequate knowledge and awareness of this unit of society conceded a better future to control allergy prevalence among children.